The Development of Implicit and Explicit Memory. - Rovee-Collier, Carolyn (John Benjamins Pub. Co., 2000)
This is the only book that examines the theory and data on the development of implicit and explicit memory. It first describes the characteristics of implicit and explicit memory (including conscious recollection) and tasks used with adults to measure them. Next, it reviews the brain mechanisms thought to underlie implicit and explicit memory and the studies with amnesics that initially prompted the search for different neuroanatomically-based memory systems. Two chapters review the Jacksonian (first in, last out) principle and empirical evidence for the hierarchical appearance and dissolution.